2018
DOI: 10.1038/s41467-018-07475-5
|View full text |Cite
|
Sign up to set email alerts
|

TRIM28 protects TRIM24 from SPOP-mediated degradation and promotes prostate cancer progression

Abstract: TRIM24 is an effector substrate of the E3 ubiquitin ligase adaptor SPOP and becomes stabilized in prostate cancer (PCa) with SPOP mutations. However, how TRIM24 protein is regulated in the vast majority of SPOP-wildtype PCa is unknown. Here we report TRIM28 as a critical upstream regulator of TRIM24. TRIM28 protein interacts with TRIM24 to prevent its ubiquitination and degradation by SPOP. Further, TRIM28 facilitates TRIM24 occupancy on the chromatin and, like TRIM24, augments AR signaling. TRIM28 promotes PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 56 publications
2
85
2
Order By: Relevance
“…The treatment of PCa has attracted increasing attention in recent years (12). Previous studies have reported numerous gene targets that were able to inhibit cell proliferation and promote apoptosis in PCa (21)(22)(23). A recent study has suggested that certain natural products, such as green tea, can effectively induce apoptosis and inhibit invasion of PCa cells via the PI3K/Akt signaling pathway (24).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of PCa has attracted increasing attention in recent years (12). Previous studies have reported numerous gene targets that were able to inhibit cell proliferation and promote apoptosis in PCa (21)(22)(23). A recent study has suggested that certain natural products, such as green tea, can effectively induce apoptosis and inhibit invasion of PCa cells via the PI3K/Akt signaling pathway (24).…”
Section: Discussionmentioning
confidence: 99%
“…Several of the EN1-interacting proteins common between the two cell lines represent transcriptional cofactors TLE3 and TRIM28 (25), and nuclear hormone receptor coactivators TRIM33 and TRIM24. Interestingly TRIM28 was recently identified as a critical regulator of TRIM24, an oncogene in prostate cancer (26) and TRIM24-TRIM28-TRIM33 complex has previously been identified as a suppressor of murine hepatocellular carcinoma growth (27). Because of prior data implying a functional role for the TLE3-EN1 interaction during development (23), we further explored the relevance of this association in breast cancer cells.…”
Section: En1 Interacting Proteins In Breast Cancer Cellsmentioning
confidence: 99%
“…To test this, we performed subcutaneous injections of A375 cells stably transduced with shT28-1 or shSCR lentivirus. Indeed, in contrast to its role in breast and prostate cancer cells 8,9 , knockdown of TRIM28 in melanoma cells led to more rapid tumor growth (Fig. 2e, f).…”
Section: Figurementioning
confidence: 89%
“…2c, d). TRIM28 has previously been reported to promote growth of breast and prostate cancer 8,9 . However, the increased levels of the mitogenic and angiogenic factors CXCL1, CXCL2 and CXCL8 17 after TRIM28 knockdown suggested that TRIM28 instead suppresses the growth of melanoma tumors.…”
Section: Figurementioning
confidence: 99%